THE CONCEPT OF DA’WAH IN CHARACTER BUILDING OF SUPERIOR GENERATION IN THE MILLENNIAL ERA-ZILLENNIAL PERSPECTIVE OF THE QUR’AN TOWARDS GOLDEN INDONESIA 2045 - Fitria, Dona; Rasyid, Daud; Oktapiani, Marliza (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
The purpose of this research is to develop the concept of da'wah in building superior generational character and da'wah strategies in building superior generational character to realize the ideals of Golden Indonesia 2045. This method uses qualitative research categorized as explanatory analysis with sociological, anthropological, philosophical, and psychological approaches. The data collection technique in this research is library research related to the problem under study. The results of this study indicate that building superior generational character towards the ideals of the Golden Indonesia 2045 requires the right strategy; therefore, da'wah and strategy development in character building from the Qur'anic perspective is the answer to the formation of a generation with superior character. “The Living Qur'an,” Muhammad Rasulullah SAW, is a figure of superior and complete character in the aspects of hard skills and skills, a model of human life in all dimensions: ideology, education, politics, economics, social, cultural, and state. Character is a behavior formed from the synergy of cognitive, affective, and psychomotor, which is inherent and spontaneous, as well as the uniqueness of each individual. A person's character is formed by primary factors; faith, and secondary factors; family, educational institutions/schools, environment and government policies. Character is a combination of a person's soft skills and hard skills competencies. The results of this study also develop the concept of da'wah specifically in realizing the Golden Indonesia 2045, namely amar ma'ruf nahi munkar through the formation of superior character of the millennial-zillennial generation with the Islamic character paradigm, where the Prophet Muhammad is a role model, a figure who is proven and tested for success throughout the ages, with universal character values. Superior character building towards Golden Indonesia 2024 is carried out through exemplary advice, direction, prohibition, orders, self-concept education (values education), habituation, consistency, and sustainability. Da'wah in shaping the superior character of the millennial-zillennial generation is carried out with 21st-century learning strategies, namely mad'u-centered learning and contextual teaching & learning, by integrating aspects of high-order thinking skills (HOTS).